Building Students' Creative Thinking Skills Using Problem- Based Learning in Handling Staple Food Waste - Handoyo, Rista Firdausa; Rosbiono, Momo; Sopandi, Wahyu (FKIP-Universitas Riau, 2021)
This study aims to build students' creative thinking skills using problem - based learning in handling staple food waste. The research methods are development and research with the stages of design, development, and evaluation. This research was conducted at a private high school in Tangerang Regency. The research was involved thirty students of Class XI IPA in the second semester of the 2019/2020 school year and was connected through the WhatsApp group. The research instrument used Student Worksheets (LKS) in the form of a test essay for nine items that have been validated to measure students’ creative thinking skills. The research data were analyzed quantitatively by using Microsoft Excel and qualitative- descriptive. The results of the students' creative thinking skills showed the percentage of fluency (31.66%), flexibility (35.18%), elaboration (58.33%), and evaluation (54.88%) indicators, the average percentage was 45.01% categorized as medium. The conclusions drawn are the creative thinking skills that emerge after using problem-based learning are fluent thinking, flexibility thinking, evaluative thinking, and elaborative thinking.